The happiest man in the world : an account of the life of Poppa Neutrino - Wilkinson, Alec, 1952- (New York : Random House, 2007)
David Pearlman, 74, is a restless and migratory soul, a mariner, a musician, a member of the Explorers Club and a friend of the San Francisco Beats, a former preacher and sign painter, a polymath, a pauper, and a football strategist for the Red Mesa Redskins of the Navajo Nation. When he recovered from a near-fatal illness at 50, he felt so different that he decided he needed a new name, and began calling himself Poppa Neutrino. He believes that each person, to be truly happy, must define his or her three deepest desires and pursue them remorselessly. Inspired by Thor Heyerdahl, Neutrino is the only man ever to build a raft from garbage he found on the streets of New York and sail it across the North Atlantic. Meanwhile, he invented an unstoppable football play, which one coach describes as being as innovative as the forward pass.--From publisher description.
English Language & Literature.
Keywords: Neutrino, Poppa, -- 1933-2011.; Eccentrics and eccentricities -- United States -- Biography; Adventure and adventurers -- United States -- Biography